STRATEGI MARKETING PEMBIAYAAN BANK SYARIAH DALAM MENDUKUNG PENGEMBANGAN UMKM DI INDONESIA - Cindy Anita Sari; Intan Azzahra; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study examines the role of Islamic banking marketing strategies in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Islamic banks have a strategic position in providing Sharia-compliant financing as an alternative source of capital for MSMEs. This research aims to analyze how financing marketing strategies implemented by Islamic banks contribute to MSME growth. A qualitative research approach is employed using SWOT analysis to identify internal strengths and weaknesses, as well as external opportunities and threats affecting the effectiveness of Sharia financing marketing. The findings indicate that compliance with Sharia principles, flexible financing contracts, strong community-based networks, and personalized services represent the main strengths of Islamic banks. However, limited understanding of Sharia contracts among MSME actors, inadequate digitalization, uneven human resource competencies, and restricted branch coverage remain internal challenges. Externally, MSME expansion, increasing demand for halal financial products, and supportive government policies provide significant opportunities, while competition from conventional banks, fintech platforms, online lending services, and low financial literacy pose serious threats. The study concludes that Islamic banks need to strengthen value-based marketing strategies rooted in Sharia principles while accelerating digital transformation. Enhancing Sharia financial literacy, developing innovative financing products, and reinforcing community-oriented marketing are recommended to improve MSME financing outreach.